2006
DOI: 10.1111/j.1399-3046.2006.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive characteristics of diabetes mellitus after hematopoietic cell transplantation during childhood

Abstract: We report on six patients who developed diabetes mellitus after hematopoietic cell transplantation (HCT). The prevalence in our cohort of long-term survivors after HCT performed below 18 yr of age was 3%. The median age at onset of diabetes was 22.4 yr (range 11.3-34.4). The median period between HCT and diabetes was 10.1 yr (range 5.6-22.1). Five out of the six patients received total irradiation therapy and five had other endocrinological abnormalities. The onset of diabetes in all patients was insidious and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…An extremely limited number of studies have reported data on abnormalities of glucose metabolism in long-term survivors after HSCT during childhood. [32][33][34][35] Many issues of diabetes mellitus in HSCT patients still remain unclear.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…An extremely limited number of studies have reported data on abnormalities of glucose metabolism in long-term survivors after HSCT during childhood. [32][33][34][35] Many issues of diabetes mellitus in HSCT patients still remain unclear.…”
Section: Diabetesmentioning
confidence: 99%
“…In a recent paper, Bonanomi et al 35 reported 6 patients in a cohort of 201 patients transplanted before age 18 years who developed diabetes mellitus at a median age of 10.1 years (range 5.6-22.1). The unique clinical and laboratory features that characterized these patients with diabetes mellitus after HSCT suggested that this should be considered as a unique and specific entity within the commonly used classifications for diabetes mellitus.…”
Section: Diabetesmentioning
confidence: 99%
“…Unique clinical and laboratory features that characterized patients with DM after HSCT suggested that this should be considered as a specific entity within the commonly used classifications for DM [7,8]. For the same reason, the treatment of DM after HSCT remains overt to discussion.…”
Section: Discussionmentioning
confidence: 99%
“…According to different reports, the occurrence of those abnormalities is quite common and reaches between 20 and 50% [1,2,3]. The occurrence of diabetes mellitus (DM) after HSCT is a relatively recent observation [4,5,6,7,8,9]. Survivors of allogeneic HSCT were 3.65 times more likely to develop diabetes than siblings and 3 times more likely than the general US population [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation